EVIDENCE FOR ISOLAPOTAMON BAUENSE NG, 1987 (DECAPODA: BRACHYURA: POTAMIDAE) BEING THE LARGEST RECORDED TRUE FRESHWATER CRAB IN SOUTHEAST ASIA - Lirong, Yu Abit; Jongkar, Grinang; Kamil, Latif (Informatics Publishing Limited, 2022)
True or primary freshwater crabs, excluding the members of Hymenosomatidae and Sesarmidae, comprise over 1,300 species in five families (Gecarcinucidae, Potamidae, Potamonautidae, Pseudothelphusidae, and Trichodactylidae), which spend their entire life in freshwater habitats and never return to the sea (Ng 2017). The key feature that differentiates all true freshwater crabs from their marine counterparts is the direct development of offspring, with no larval stages, i.e., their eggs hatch directly into young crabs (Ng 2017; Sternberg and Cumberlidge 2001; Yeo et al. 2008). Their high level of endemicity, low fecundity rates, limited dispersal, and fragmented distribution throughout freshwater ecosystems are major factors which make true freshwater crabs among the most threatened species, especially in the tropics (Cumberlidge et al. 2009).